The FuGas 2.5 updated for the effects of surface turbulence on the transfer velocity of gases at the atmosphere–ocean interface - Vieira, Vasco M. N. C. S. (2020)
Accurately estimating air–water gas exchanges requires considering other factors besides wind speed. These are particularly useful for coastal ocean applications, where the sea-state varies at fine spatial and temporal resolutions. We upgrade FuGas 2.5 with improved formulations of the gas transfer velocity parametrized based on friction velocity, kinetic energy dissipation, roughness length, air-flow conditions, drift current and wave field. We then test the algorithm with field survey data collected in the Baltic Sea during spring–summer of 2014 and 2015. Collapsing turbulence was observed when gravity waves were the roughness elements on the sea-surface, travelling at a speed identical to the wind. In such cases, the turbulence driven transfer velocities (from surface renewal and micro-scale wave breaking) could be reduced from 20 cm h1 to 5 cm h1. However, when peak gravity waves were too flat, they were presumably replaced by capillary-gravity waves as roughness elements. Then, a substantial increase in the turbulence and roughness length was observed, despite the low and moderate winds, leading to transfer velocities up to twice as large as those predicted by empirical u10-based formulations.